An integrated multiplatform bioanalytical strategy for antibody–drug conjugates: a novel case study. (August 2015) - Myler, Heather; Rangan, Vangipuram S; Wang, Jian; Kozhich, Alexander; Cummings, Jennifer A; Neely, Robert; Dail, Donna; Liu, Ang; Wang, Bonnie; Vezina, Heather E; Freebern, Wendy; Sung, Mei-Chen; et al.
Background: The bioanalytical strategy for antibody–drug conjugates (ADC) includes numerous measurements integrally designed to provide comprehensive characterization of PK, PD and immunogenicity. This manuscript describes the utilization of reagents specifically tailored to an ADC with a microtubule polymerization inhibitor payload and cathepsin B cleavable linker.Methods: The PK strategy includes the evaluation of physiological levels of total antibody, active ADC, total ADC, antibody-conjugated payload and unconjugated payload. These data are evaluated in the context of target and antidrug antibody levels to elucidate bioactive ADC.Results & conclusion: Herein, we discuss how this strategy has been applied and present our preliminary observations. Continuously evolving to meet pipeline demands, the integrated bioanalytical data will provide critical insights into the exposure–response relationship.